Instilling Core Islamic Values in Industrial Relations in Malaysia - Zakiyy, Norman (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Instilling religious values in maintaining good industrial relations is a much neglected area of study in industrial jurisprudence. Evidently, trade disputes are usually referred to the Industrial Court whereby resolution of disputes are usually based on the reference of relevant Industrial Court awards, civil court judgments, statutes and best practices for industrial harmony. However, little emphasis has been given to religion as an important tool for resolving conflicts among mankind. Thus, the objective of this study is to identify core Islamic values relevant in maintaining good industrial relations in Malaysia. The trans-disciplinary approach was chosen to correlate core Islamic values in meeting the two different sets of expectations; one of the employer and the other by the employee. The methodology used is legal and content analysis of Industrial Court awards, case laws, relevant statutes and the Qur’an being the primary source of the Shariah. The main finding of the study indicates that core Islamic values such as purity of intentions, contentment, patience and consultation are essential components in enhancing the harmonious relationship between the employer and the employee; apart from gaining spiritual satisfaction. Hence, future studies on religion as an important component of industrial relations law alongside other well-established components, namely economics, sociology and politics. Keywords- Islam; Industrial Relations law; Malaysia; Religious values